Knowledge sharing practices: A case study of academic staff at a community college in Sarawak - Zulina, Kamarulzaman (Universiti Malaysia Sarawak (UNIMAS), 2011)
Knowledge is vital to human life. Knowledge can be easily acquired through formal or informal learning. Sharing knowledge is one of the most important components in knowledge management. This study aims to investigate whether knowledge sharing is practiced by the employees, particularly academic staff at the community college in Sarawak. The study examined six informants whose demographic factors include age, gender, educational background and years of service to the community college; . Based on the results of the study, all informants agreed that the practice of knowledge sharing is a matter that is common in organizations where it is beneficial not only to individuals but also to the management. However, there are several kinds of knowledge and information that employees are not willing to share, and this is a barrier to knowledge sharing practices in the organization. It is recommended that future studies should increase the number of samples and include the support staff, whether from the public or private sectors to compare the findings.